COMPARATIVE AND CROSS-SECTIONAL STUDY OF SUCCESSES OF THE LEPROSY ELIMINATION STRATEGY BEFORE (2000 TO 2005) AND AFTER (2006 TO 2010) ERADICATION PERIOD IN REFERRAL HOSPITAL OF TAMIL NADU - Arun, Sundaramoorthy; Balachandar, Vellingiri; Sasikala, Keshavarao; Subramanian, Arunachalam; Abilash, Valsala Gopalakrishnan (Asian Journal of Pharmaceutical and Clinical Research, 2013)
To assess the successes of the leprosy elimination strategy before (2000 to 2005) and after (2006 to 2010) eradication period in referral hospital of Tamilnadu District. Retrospective cross-sectional study of all registered new cases of leprosy carried out from records over a ten year period from referral Sacred heart leprosy hospital, Kummbakkonam, Tamil Nadu. During the survey, total number of 5,794 new leprosy cases registered during 2000 to 2010 between before and after eradication period at referral leprosy hospital. Comparative analysis of 5 years of before and after eradication period survey shows that the total number of multibacillary and paucibacillary cases registered before eradication was 4177and after eradication it was reduced to1617, in that multibacillary cases reduced from 2724 to 1150 after eradication and paucibacillary cases reduced from 1453 to 467 cases. According to this analysed report concluding that the total number of leprosy cases reported in referral hospital per day before eradication was 2.28 and after eradication it was reduced to 0.88 cases per day. Leprosy was still an important public health problem and was getting out of control in some districts in Tamil Nadu, south India. However, leprosy elimination is well within sight, and after eradication period also risk of the leprosy cases in endemic districts. So leprosy awareness days and community-based surveillance could help to improve early detection, treatment, case holding and prevention of disabilities. Increase the awareness program for endemic districts is a very well method in decrease the leprosy. Keywords: Leprosy, Multibacillary, Paucibacillary, Multi Drug Therapy